(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
This paper presents an analysis of the effect of free vibrations of a free-free beam, fixed-fixed beam and simply supported beam using the series solution. It was found that the mode shape for each of the modes has effects on the displacement or deflection of such beam so that the deflection increases as the increase of the mode. Also, a Simply-Supported beam has a lower displacement compared to the free-free beam and fixed-fixed beam which almost have the same displacement. At mode one, it is seen that a Simply Supported beam has a higher amplitude, followed by a free-free beam and then a fixed-fixed beam.